A Novel Mining Method for Longwall Panel Face Passing through Parallel Abandoned Roadways - Yang Li; Yuqi Ren; Nan Wang; Junbo Luo; Na Li; Yikun Liu; Guoshuai Li (Shock and Vibration)
Mining pressure behavior in the process of longwall panel face passing through the parallel abandoned roadways (PARs) is different from the ordinary longwall panel face. It is easy to induce the accident of roof falling, coal wall spalling, and crush accident of shield. In order to reduce the occurrence of mine pressure accidents and ensure safe mining, a new mining method named “swing-inclined” mining method was proposed and was employed in the E13103 of Cuijiazhai coal mine. Based on the process of the longwall panel face passing through the PARs, a long-span and multisupport mass-structure model of the roof was established. The maximum support capacity of shield was calculated combined with stability relation between “roof-shield-PAR-‘similar pillar (SP)’-coal wall.” It provided the basis for determining the reasonable support capacity of shield. Moreover, the sensitivity analysis of influenced factors to the maximum support capacity of shield was carried out by using Matlab software. The sensitivity analysis results indicated that different factors had a different effect on the support capacity of shield. And, the process of passing through the PARs can be divided into 3 stages, depending on the relation between support capacity of shield and width of SP. In different stages, the change degree of support capacity of shield was different. The support capacity of shield is mainly influenced by the hanging distance of the main roof and the horizontal distance between the support point of the coal wall and the breaking position of the main roof. By on-site measurement, the sensitivity analysis results were verified.